The Theoretical Description for Ibotenic Acid and Muscimol Electrochemical Determination in Mushroom Pulp and Mushroom-based Alcoholic Beverages on Nano- CuS Composite with Conducting Polymer - Tkach, V. V.; Kushnir, M. V.; Romaniv, L. V.; de Oliveira, S. C.; Ivanushko, Y. G.; Nazymok, Ye. V.; Ahafonova, O. V.; Yagodynets, P. I.; da Silva, A. O.; Derevianko, N. P.; Zavhorodnii, M. P.; Odyntsova, V. M.; et al. (My University, 2024)
In this article, the possibility for ibotenic acid and muscimol electrochemical determination on the electrode, modified by nano-CuS/conducting polymer composite, is theoretically described. The analytical signal is based on the reaction of the copper (III) sulfohydroxide with both of the analytes, and the reaction is realized by two parallel scenarios. The analysis of the correspondent model confirms the possibility of the oscillatory behavior caused by DEL influence of the electrochemical stage and chemical stage involving ibotenic acid. The chemical stages involving muscimol do not participate in the oscillatory behavior. The stability analysis confirms the easy realization of the linear dependence between the electrochemical parameter and concentration and, therefore, the facility in analytical signal interpretation.
Keywords: Amanita muscaria; ibotenic acid; muscimol; electrochemical sensor; conducting polymer; copper (II) sulfide; stable steady-state